2016
DOI: 10.3177/jnsv.62.198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enzyme-Treated Asparagus Extract (ETAS) on Psychological Stress in Healthy Individuals

Abstract: The aim of this study was to examine the effectiveness of Enzyme-Treated Asparagus Extract (ETAS) on improving stress response. A randomized, double-blind, placebo-controlled cross-over trial was undertaken in healthy volunteers. ETAS (150 mg/d) or a placebo was consumed for 28 d, with a washout period. Psychological parameters were examined using a self-report scale questionnaire and psychological stress was applied using the Uchida-Kraepelin (U-K) test. During the stress load, autonomic nervous function was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Ongoing analysis suggested that ETAS 50 contains proline-containing 3-alkyldiketopiperazine derivatives as its active compounds. When ETAS 50 was orally administered, it attenuated sleep deprivation-induced stress responses, promotes good sleep, and increases salivary secretory immunoglobulin A levels in mice and humans [ 13 15 ]. These previous findings suggest a possibility that the compounds or their metabolites are delivered to central nervous system via circulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing analysis suggested that ETAS 50 contains proline-containing 3-alkyldiketopiperazine derivatives as its active compounds. When ETAS 50 was orally administered, it attenuated sleep deprivation-induced stress responses, promotes good sleep, and increases salivary secretory immunoglobulin A levels in mice and humans [ 13 15 ]. These previous findings suggest a possibility that the compounds or their metabolites are delivered to central nervous system via circulation.…”
Section: Resultsmentioning
confidence: 99%
“…ETAS 50 is a standardized extract from the Asparagus officinalis stem, produced by Amino Up Chemical Co. Ltd. (Sapporo, Japan). It is a unique eco-friendly functional food that attenuates sleep deprivation-induced stress responses, promotes good sleep, and increases salivary secretory immunoglobulin A levels in mice and humans [ 13 15 ]. In addition to its antistress effects, later studies demonstrated the beneficial effects of ETAS 50 on brain functions, including the ability to ameliorate cognitive impairment in senescence-accelerated mice [ 16 ], protect neuronal PC-12 cells from amyloid β -induced cytotoxicity [ 17 ], and improve learning ability in young healthy rats [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to be a novel and unique functional food that attenuates sleep deprivation-induced stress responses and promotes sleep in mice and humans [ 14 , 15 ]. A recent study also showed that ETAS 50 supplementation reduced the feelings of dysphoria and fatigue, ameliorated the quality of sleep, and enhanced stress-load performance as well as increasing salivary secretory immunoglobulin A levels in healthy adults [ 16 ]. In addition to these anti-stress effects, ETAS 50 has antiaging potencies via its ability to ameliorate cognitive impairment in senescence-accelerated mice [ 17 ], to protect neuronal PC-12 cells from amyloid β peptide-induced oxidative stress and cytotoxicity [ 18 ], and to improve learning ability in young healthy rats [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This previous finding suggests that the compounds or their metabolites directly act on the cells and induce HSP70 expression. Moreover, oral EAS intake attenuated sleep deprivation-induced stress responses, promoted good sleep, and increased salivary secretory immunoglobulin A levels in mice and humans [ 5 , 7 , 12 ]. Therefore, it is conceivable that the compounds or their metabolites are delivered to central nervous system after digestion ingestion via circulation.…”
Section: Resultsmentioning
confidence: 99%